Advances in the study of Müller glia reprogramming in mammals - Guo, Yi-Ming; Jiang, Xinyi; Min, Jie; Huang, Juan; Huang, Xiu-Feng; Ye, Lu (Frontiers in Cellular Neuroscience, 2023)
Müller cells play an integral role in the development, maintenance, and photopic signal transmission of the retina. While lower vertebrate Müller cells can differentiate into various types of retinal neurons to support retinal repair following damage, there is limited neurogenic potential of mammalian Müller cells. Therefore, it is of great interest to harness the neurogenic potential of mammalian Müller cells to achieve self-repair of the retina. While multiple studies have endeavored to induce neuronal differentiation and proliferation of mammalian Müller cells under defined conditions, the efficiency and feasibility of these methods often fall short, rendering them inadequate for the requisites of retinal repair. As the mechanisms and methodologies of Müller cell reprogramming have been extensively explored, a summary of the reprogramming process of unlocking the neurogenic potential of Müller cells can provide insight into Müller cell fate development and facilitate their therapeutic use in retinal repair. In this review, we comprehensively summarize the progress in reprogramming mammalian Müller cells and discuss strategies for optimizing methods and enhancing efficiency based on the mechanisms of fate regulation.